The relative and joint effects of gunshot detection technology and video surveillance cameras on case clearance in Chicago - Piza, Eric L. (Criminology & public policy, 2025)
Research Summary Closed-circuit television (CCTV) video surveillance cameras and gunshot detection technology (GDT) have been widely adopted by police departments in recent years. Most evaluation research on CCTV and GDT has tested the technologies’ effect on crime prevention rather than case clearance rates. The current study contributes to the literature through a matched quasi-experiment of the relative and joint effect of GDT and CCTV on fatal and nonfatal shooting investigation outcomes in Chicago, IL. Entropy balancing is used to create a weighted control group that closely resembles the treatment group. Logistic regression models incorporating the weights from the entropy matching procedure as probability weights measure the intervention effects. Treatment conditions generated null findings across all models. Although included as a control variable in the models, Chicago's Strategic Decision Support Centers (SDSCs) were positively associated with case clearance in the nonfatal shooting models. Policy Implications These findings contribute to the knowledge base on police use of technology in gun violence investigations. Similar to prior research, results indicate that technology may not deliver the crime control benefits policy makers anticipate they will receive from their investments. Gun violence represents the United States’ most critical crime problem, with the decrease in clearance rates garnering significant attention in both the academic and practitioner communities. The current study suggests that investments in technology on their own may not directly improve case clearance rates. However, the findings regarding SDSCs indicate they may be a promising model for leveraging the outputs of multiple technologies to assist gun violence investigations. Increased resources should be dedicated to rigorously testing the effect of SDSCs on gun violence investigation outcomes.